Release of parasitic wasps to control stable flies in Kansas dairies - G. L. Greene (Kansas Agricultural Experiment Station Research Reports, 1991)
After release of fly parasites in Kansas dairies during 1991, parasitism increased from May to late June then dropped in July. The parasite released was Spalangea nigroaenea of Kansas origin to assure its adaption to Kansas conditions. Additional studies of fly parasite releases are needed to develop a reliable fly reduction program for Kansas dairies before fly parasite purchases can be reliably recommended. Release of adapted parasite species and removal of fly breeding areas will be essential for reduction of fly numbers at Kansas dairies.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Fly parasites